2015
DOI: 10.4012/dmj.2015-017
|View full text |Cite
|
Sign up to set email alerts
|

Push-out bond strength of CPP-ACP-modified calcium silicate-based cements

Abstract: This study evaluated the push-out bond strength of 0%, 0.5%, 1.0%, 2.0% and 3.0% (w/w) casein phosphopeptide-amorphous calcium phosphate (CPP-ACP)-modified calcium silicate-based cements (CSCs). The push-out bond strength of a trial MTA was also compared with two CSCs (Biodentine ™ and Angelus ® MTA). Three hundred 1 mm thick horizontal root sections were prepared from 60 singlerooted human teeth. The canal space of each section was enlarged and filled with the cements. The sections were stored in a phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…Biodentine also had significantly higher bond strength than ProRoot MTA in coronal dentin. These findings are similar to those of previous studies [16,19,20] . Guneser et al [16] demonstrated that Biodentine showed significantly higher bond strength than MTA, and exposure to various endodontic irrigants did not affect this finding negatively.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Biodentine also had significantly higher bond strength than ProRoot MTA in coronal dentin. These findings are similar to those of previous studies [16,19,20] . Guneser et al [16] demonstrated that Biodentine showed significantly higher bond strength than MTA, and exposure to various endodontic irrigants did not affect this finding negatively.…”
Section: Discussionsupporting
confidence: 83%
“…Adhesive bond failures in the Biodentine group were slightly less common when compared to ProRoot MTA. These findings are partly in agreement with previous studies that reported adhesive failures for ProRoot MTA and cohesive failures for Biodentine [6,16,20] . The predominantly mixed failures observed for BioAggregate could have been due to weak cement or incomplete setting resulting in poor physical properties.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…2 Several studies evaluating the properties of TCSs used body fluid simulation solutions such as phosphate-buffered saline, 21,22,34 Hank's balanced salt solution to store the setting cement before testing. 2 Several studies evaluating the properties of TCSs used body fluid simulation solutions such as phosphate-buffered saline, 21,22,34 Hank's balanced salt solution to store the setting cement before testing.…”
Section: Tested Tricalcium Silicate Cement Considerationsmentioning
confidence: 99%
“…The physicochemical properties of TCSs are also influenced by different types of storage media. 2 Several studies evaluating the properties of TCSs used body fluid simulation solutions such as phosphate-buffered saline, 21,22,34 Hank's balanced salt solution to store the setting cement before testing. 35,36 This phosphate containing synthetic tissue fluids could negatively affect the setting of TCSs.…”
Section: Tested Tricalcium Silicate Cement Considerationsmentioning
confidence: 99%